Penerapan Enterprise Architecture untuk Integrasi Sistem Informasi Pendidikan: Studi Literatur - Angeline; Loren, Friska; Angelo, Jacky; Tania, Sully (Yayasan Pendidikan Penelitian Pengabdian Algero, 2024)
Education is one of the fields that plays a significant role in the development of individuals and society. In some educational institutions, there are still issues, such as challenges in managing student data, lack of educator performance, and others. Therefore, the implementation of information technology has a profound impact on improving the management of university and school systems. Each educational institution should have standards to enhance business agreements and strategies. Enterprise Architecture can be utilized by schools and universities to facilitate the student admission process through the implementation of various systems. The results of the journal evaluation show that the majority of research studies use TOGAF (The Open Group Architecture Framework) as a framework to generate an Enterprise Architecture blueprint that can be utilized for integrating information systems, thus demonstrating that the implementation of enterprise architecture can influence the improvement of business process efficiency in the education sector. Additionally, there are differences in frameworks among previous studies, such as the utilization of Enterprise Architecture Planning and Federal Enterprise Architecture Framework. Each research journal also presents certain strengths and weaknesses, such as the ineffectiveness of including required cost estimates, among others.